The association and a potential pathway between gender-based violence and induced abortion in Thai Nguyen province, Vietnam - Phuong Hong Nguyen; Son Van Nguyen; Manh Quang Nguyen; Nam Truong Nguyen; Sarah Colleen Keithly; Lan Tran Mai; Loan Thi Thu Luong; Hoa Quynh Pham (Taylor & Francis Group, 2012)
Background: Gender-based violence (GBV) has profound adverse consequences on women's physical, mental, and reproductive health. Although Vietnam has high rates of induced abortion and GBV, literature examining this relationship is lacking. Objective: This study examines the association of GBV with induced abortion among married or partnered women of reproductive age in Thai Nguyen province, Vietnam. In addition, we explore contraceptive use and unintended pregnancy as mediators in the pathway between GBV and induced abortion. Design and methods: Data were drawn from a cross-sectional survey of 1,281 women aged 18–49 years in four districts of Thai Nguyen province. Bivariate and multivariate logistic regression analyses were applied to examine the associations between lifetime history of GBV, contraceptive use, unintended pregnancy, induced abortion, and repeat abortion, controlling for other covariates. Results: One-third of respondents had undergone induced abortion in their lifetime (33.4%), and 11.5% reported having repeat abortions. The prevalence of any type of GBV was 29.1% (17.0% physical violence, 10.4% sexual violence, and 20.1% emotional violence). History of GBV was associated with induced abortion (OR=1.61, 95% CI: 1.20–2.16) and repeat abortion (OR=2.22, 95% CI: 1.48–3.32). Physical violence was significantly associated with induced abortion, and all three types of violence were associated with repeat abortion. Abused women were more likely than non-abused women to report using contraceptives and having an unintended pregnancy, and these factors were in turn associated with increased risk of induced abortion. Conclusions: GBV is pervasive in Thai Nguyen province and is linked to increased risks of induced abortion and repeat abortion. The findings suggest that a pathway underlying this relationship is increased risk of unintended pregnancy due in part to ineffective use of contraceptives. These findings emphasize the importance of screening and identification of GBV and incorporating women's empowerment in reproductive health and family planning programs.